Boron Nitride Nanosheets Improve Sensitivity and Reusability of Surface‐Enhanced Raman Spectroscopy. Issue 29 (26th April 2016) - Cai, Qiran; Mateti, Srikanth; Yang, Wenrong; Jones, Rob; Watanabe, Kenji; Taniguchi, Takashi; Huang, Shaoming; Chen, Ying; Li, Lu Hua
Abstract: Surface enhanced Raman spectroscopy (SERS) is a useful multidisciplinary analytic technique. However, it is still a challenge to produce SERS substrates that are highly sensitive, reproducible, stable, reusable, and scalable. Herein, we demonstrate that atomically thin boron nitride (BN) nanosheets have many unique and desirable properties to help solve this challenge. The synergic effect of the atomic thickness, high flexibility, stronger surface adsorption capability, electrical insulation, impermeability, high thermal and chemical stability of BN nanosheets can increase the Raman sensitivity by up to two orders, and in the meantime attain long‐term stability and extraordinary reusability not achievable by other materials. These advances will greatly facilitate the wider use of SERS in many fields. Abstract : BN provides silver SERvice : Atomically thin boron nitride (BN) nanosheets coated onto silver nanoparticles improve the sensitivity, reproducibility, stability, and reusability of surface‐enhanced Raman spectroscopy (SERS).